Optimization of Human Resources of State Civil Apparatus in Facing the Era of Disruption - Yulianah, Yulianah (International Journal of Demos (IJD), 2025)
Abstract The rapid development of technology in the disruption era has brought both challenges and opportunities for the government sector, particularly in improving the quality and performance of Civil apparatus. This study aims to analyze strategies for optimizing human resources of civil apparatus in facing the disruption era, highlighting the factors that influence the readiness and capability of civil apparatus in responding to the increasingly digital and dynamic work environment. The method used in this research is a descriptive qualitative approach, with data collection techniques including in-depth interviews, observations, and documentation studies at selected government institutions. The results show that optimizing Human Resources of Civil apparatus in the face of the disruption era largely depends on the integrated enhancement of digital, managerial, and socio-cultural competencies. civil apparatus equipped with information technology skills, leadership ability in a digital ecosystem, as well as an understanding of national values and cultural diversity tend to be more adaptive and productive in carrying out public service duties. In addition, the implementation of a merit system, collaborative work culture, and the utilization of technologies such as e-learning, e-performance, and e-recruitment significantly accelerate bureaucratic transformation towards a more modern and efficient direction. Government policy support, as well as collaboration with educational institutions, the private sector, and digital communities, also prove to be strengthening factors in sustainably expanding civil apparatus capacity development. Keywords: Human Resources, Civil Apparatus, Optimization, Disruption Era, Digital Competency.